Effect of a nutritional counseling activities, by using a social network, in coping with obesity - Corrêa, Mariana Aparecida Fulanette; Verde, Andressa Lemes Vila; Sugizaki, Clara Sandra de Araújo; Freitas, Ana Tereza Vaz de Souza; Sagno, Adriana Luz Martins; Schincaglia, Raquel Machado; Sousa, Lucilene Maria de; Menezes, Ida Helena Carvalho Francescantonio (O Mundo da Saúde, 2022)
Innovative strategies need to be adopted to combat the growing prevalence of obesity. Thus, the aim of this study is to evaluate the effect of a nutritional counseling activity using a social network in coping with obesity. This is a before-and-after experimental study, including 60 overweight individuals enrolled in a Primary Care Center. It was carried out from June to October 2020. Educational actions (sharing information about healthy eating and health and agreeing on challenges) were carried out through the WhatsApp® application, weekly, for 16 weeks. Sociodemographic, economic, clinical, anthropometric, food consumption, and biochemical data were collected. Data were compared by the Wilcoxon or Kappa test. Most participants were female and 36.4% had a diagnosis of hypertension. After the intervention, there was a reduction in waist circumference (before:107.3±11.4; after:105.6±11.5 cm, p=0.004), total cholesterol (before:205.9±48, 3; after:191.5±34.3 mg/dL, p<0.001), and LDL-c (before:132.4±37.8; after:120.2±29.3 mg/dL, p<0.001). The activity was able to promote reductions in body markers of obesity and metabolic imbalances associated with obesity, demonstrating the importance of innovative interventions that can add to other interventions and facilitate public adherence.